Highly siderophile element (HSE) abundances in the mantle of Mars are due to core formation at high pressure and temperature. (6th January 2015) - Righter, K.; Danielson, L. R.; Pando, K. M.; Williams, J.; Humayun, M.; Hervig, R. L.; Sharp, T. G.
Abstract Highly siderophile elements (HSEs) can be used to understand accretion and core formation in differentiated bodies, due to their strong affinity for FeNi metal and sulfides. Coupling experimental studies of metal–silicate partitioning with analyses of HSE contents of Martian meteorites can thus offer important constraints on the early history of Mars. Here, we report new metal–silicate partitioning data for the PGEs and Au and Re across a wide range of pressure and temperature space, with three series designed to complement existing experimental data sets for HSE. The first series examines temperature effects for D(HSE) in two metallic liquid compositions—C‐bearing and C‐free. The second series examines temperature effects for D(Re) in FeO‐bearing silicate melts and FeNi‐rich alloys. The third series presents the first systematic study of high pressure and temperature effects for D(Au). We then combine our data with previously published partitioning data to derive predictive expressions for metal–silicate partitioning of the HSE, which are subsequently used to calculate HSE concentrations of the Martian mantle during continuous accretion of Mars. Our results show that at midmantle depths in an early magma ocean (equivalent to approximately 14 GPa, 2100 °C), the HSE contents of the silicate fraction are similar to those observed in the Martian meteorite suite. This is in concert with previous studies on moderately siderophile elements. We then consider model calculations that examine the role of melting, fractional crystallization, and sulfide saturation/undersaturation in establishing the range of HSE contents in Martian meteorites derived from melting of the postcore formation mantle. The core formation modeling indicates that the HSE contents can be established by metal–silicate equilibrium early in the history of Mars, thus obviating the need for a late veneer for HSE, and by extension volatile siderophile elements, or volatiles in general.